Friction between hand and different surfaces under different conditions and its implication for sport climbing - Fuss, F. K.; Niegl, G.; Tan, A. M. (The Engineering of Sport 5, Volume 2, 2004)
Friction between hand and hold is essential for sport climbing and the use of `chalk` (MgCO3) during climbing usually increases friction. The purpose of this study was to determine the friction coefficient between hand and different surfaces (artificial climbing hold, sandpaper, Perspex), and under different conditions (dry or wet hand, hand covered with powder chalk or liquid chalk, clean or messy surface). The surfaces and conditions were tested on a mini force plate. The normal and tangential forces, the friction coefficients (ì), as well as the centers of pressure (COP) were calculated from the force and moment equilibrium of the collected data. The static friction coefficient was determined by plotting ì versus COP and a number of observations were made. Powder chalk is significantly better than liquid chalk for all surfaces. The use of powder chalk on the artificial hold and Perspex is significantly better than a clean, dry hand. For the artificial handhold, we obtained 3 pairs of results: there is no difference between dry hand and liquid chalk; dry and wet hand; powder chalk and messy surface. In addition, it was noticed that the friction coefficient was highest when only one side, either the hand or the surface, is powdered and the other side left dry, regardless of the type of surface. Climbers consequently should use powder chalk instead of liquid chalk on a clean surface, but no chalk on a chalk-polluted surface.